Flood Hazards in Metro Manila: Recognizing Commonalities, Differences, and Courses of Action - Zoleta-Nantes, Doracie B. (Social Science Diliman: A Philippine Journal of Society and Change; Vol 1 No 1 (2000), 2007)
This paper looks at the vulnerability to flood hazards of different urban groups in Metro Manila, the Philippines. It contextualizes and finds similarities and differences in the physical, social, economic and institutional manifestations of severe flood hazards to three groups of people in the mega-city. They are the street children and residents of wealthy neighborhoods and urban poor settlements. It explicates a set of issues that needs to be confronted and a list of appropriate actions that can be taken to initiate a pro-active stance in dealing with the causes and consequences of flood hazards at the local scale. This is necessary for future development planning and hazard mitigation purposes.